Tales of a fourth grade nothing - Blume, Judy.; Doty, Roy, 1922- (New York : Dutton Children's Books, 2002)
Peter finds his demanding two-year-old brother an ever-increasing problem.
Elem. School Library Collection
School Library Journal
Wilson's Children
4.9
3-6.
3-6
Keywords: Brothers -- Fiction; Family life -- Fiction; Humorous stories; Brothers -- Fiction; Family life -- Fiction; Humorous fiction